Созвездие стрельца: роман / Анна Берсенева - Берсенева Анна Александровна (Анна Берснева, 2017)
Экземпляры: ф.15 (20190418) / Инвентарный номер: 59475 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 51 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44